RANCANG BANGUN ROBOT MOBIL LINE FOLLOWER PENGANTAR BERKAS DI KANTOR MENGGUNAKAN ANDROID - Murshal Firdany; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2022)
This is the era of very advanced technology , robots are one of the most useful tools for humans. This is useful for helping humans in all things work to be faster and more efficient. Which in this Covid-19 pandemic condition we are required to keep our distance from one another. PT. B'right PLN Batam is one of the leading energy companies in Batam which still uses a manual system in sending files. With this line follower car, it will be able to ease the work of employees in PT. B'right PLN Batam, and can reduce direct contact with other people in this pandemic condition. This study aims to design a line follower mobile robot to deliver files at the office using Android to help deliver files quickly and efficiently. The method used in this research is to utilize the MIT app inventor, which is used to design and control robots on Android Smartphones. The programming used to control this robot is Arduino. There are several important parts in this line follower car, namely Arduino, sensors, and drivers. With the Line Follower Car Robot, it is expected to be able to help employees of PT. B'right PLN Batam in carrying ourtheir duties.